(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the ethnolinguistic features of the use of Uzbek anthroponyms with forms of the possessive category in a comparative aspect with German anthroponyms. The possessive form appears in different paradigms in two unrelated languages. In the Uzbek language, possessive pronouns and possessive suffixes give possessive meaning, while in German only a possessive pronoun is used to express the meaning of possessiveness. Also in the Uzbek language, which is considered a Turkic language, even if the possessive pronoun is omitted, the possessive meaning is understood using a possessive suffix, but this situation is not typical for the German language, which is part of the Germanic language group.Possessive forms are usually not used with anthroponyms, but when they occur with anthroponyms, they express different connotative meanings in the Uzbek language.